2020
DOI: 10.1152/jn.00240.2020
|View full text |Cite
|
Sign up to set email alerts
|

Increased cerebral blood flow supports a single-bout postexercise benefit to executive function: evidence from hypercapnia

Abstract: A single bout of aerobic exercise improves executive function; however, the mechanism for the improvement remains unclear. One proposal asserts that an exercise-mediated increase in cerebral blood flow (CBF) enhances the efficiency of executive-related cortical structures. Here, participants completed separate 10-min sessions of moderate to heavy intensity aerobic exercise, a hypercapnic environment (i.e., 5% CO2), and a non-exercise and non-hypercapnic control condition. The hypercapnic condition was included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 75 publications
3
29
0
Order By: Relevance
“…Instead, our findings add to convergent literature asserting that a single bout of exercise improves executive function (Chang et al, 2012 ; Lambourne & Tomporowski, 2010 ; Ludyga et al, 2016 ). As indicated in the Introduction, the improvement may reflect an exercise-mediated increase in cerebral blood flow (Lucas et al, 2012 ; Tari et al, 2020 ), biomolecule concentration (Knaepen et al, 2010 ; Zouhal et al, 2008 ) and/or resting state functional connectivity that enhances the efficiency and effectiveness of the local neural circuitry supporting executive function (i.e., the hemo-neural hypothesis; see Moore & Cao, 2008 ). Regardless of the mechanism, or mechanisms, the magnitude of the pre- to postexercise decrease in antipointing RT and reported effect size (d z = 0.90) is markedly similar to five previous studies employing a lab-based assessment of antisaccade performance (i.e., average postexercise RT reduction of 21 ms with a pooled effect size of 1.01) (Dirk et al, 2020 ; Heath et al, 2018 ; Petrella et al, 2019 ; Samani & Heath, 2018 ; Tari et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Instead, our findings add to convergent literature asserting that a single bout of exercise improves executive function (Chang et al, 2012 ; Lambourne & Tomporowski, 2010 ; Ludyga et al, 2016 ). As indicated in the Introduction, the improvement may reflect an exercise-mediated increase in cerebral blood flow (Lucas et al, 2012 ; Tari et al, 2020 ), biomolecule concentration (Knaepen et al, 2010 ; Zouhal et al, 2008 ) and/or resting state functional connectivity that enhances the efficiency and effectiveness of the local neural circuitry supporting executive function (i.e., the hemo-neural hypothesis; see Moore & Cao, 2008 ). Regardless of the mechanism, or mechanisms, the magnitude of the pre- to postexercise decrease in antipointing RT and reported effect size (d z = 0.90) is markedly similar to five previous studies employing a lab-based assessment of antisaccade performance (i.e., average postexercise RT reduction of 21 ms with a pooled effect size of 1.01) (Dirk et al, 2020 ; Heath et al, 2018 ; Petrella et al, 2019 ; Samani & Heath, 2018 ; Tari et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Post-assessment pro- and antipointing trials were completed ~ 4-min after the end of the exercise and control sessions. The basis for the 4-min delay was to allow HR in the exercise session to fall below 100 bpm and is the same protocol used in previous lab-based and continuous HR monitoring studies by our group (Dirk et al, 2020 ; Heath et al, 2018 ; Petrella et al, 2019 ; Shukla & Heath, 2021 ; Tari et al, 2020 ). Each pro- and antipointing assessment required approximately 12-min to complete.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One important mechanism that may explain the effects of physical activity on cognitive performance is changes in blood circulation in the cerebral cortex, especially in the frontal lobe (prefrontal), which is involved in solving cognitively demanding tasks [ 16 , 17 ], but the majority of research has been in adults. Generally, results have revealed that a single bout of exercise can elicit immediate cognitive task-related increases on cerebral blood flow post exercise cessation [ 18 22 ], but also decreases or no effects have been observed [ 23 , 24 ]. Reasons for differing results are partly related to the moderating effects of timing, duration, and intensity of the physical activity, and the timing and type of cognitive test performed.…”
Section: Introductionmentioning
confidence: 99%